Pengembangan Guru Pembimbing Khusus sebagai Strategi Meningkatkan Kualitas Pelayanan Pendidikan Inklusif di Madrasah Ibtidaiyah - Anna Akhirul Rokhmawati; Wiwik Dwi Hastuti; Ranti Novianti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine in depth the role of special guidance teachers at Madrasah Ar Roihan in implementing inclusive learning, as well as to analyze the pedagogical strategies applied in educating students with special needs. The implementation of inclusive education requires attention to a number of fundamental aspects, including the provision of a safe, comfortable, and friendly classroom environment for all students, including those with special needs. In addition, it is important to foster a school culture that upholds the values ​​given to differences and acceptance of diversity. The results of the study indicate that special guidance teachers have been able to create a learning atmosphere that supports the active participation of students with special needs. To gain a comprehensive understanding of the dynamics of inclusive learning, the researcher conducted direct observations of classroom learning activities. These findings indicate the need for further training for special guidance teachers, in order to strengthen their professional competence in managing inclusive classes, designing adaptive curricula, and implementing learning strategies that are responsive to the individual needs of students. Therefore, this study emphasizes the importance of providing ongoing support for the development of the capacity of special guidance teachers, as a strategic effort to improve the quality of the implementation of inclusive education in educational units.